Reforming Capital Taxation in Italy - Eyraud, Luc (IMF Working Papers; Working Paper, 2014)
This paper reviews capital taxation issues in Italy based on a comprehensive definition encompassing taxes on income, transactions, and ownership. It discusses options to enhance the neutrality of the capital income tax system, followed by a detailed analysis of the property tax, the inheritance tax, and various transaction taxes. The paper also examines the case for replacing the set of existing taxes on financial and real assets with a single net wealth tax.